The spleen as a possible source of serine protease inhibitors and migrating monocytes required for liver regeneration after 70% resection in mice - Elchaninov, Andrey; Vishnyakova, Polina; Kuznetsova, Maria; Gantsova, Elena; Kiseleva, Viktoria; Lokhonina, Anastasiya; Antonova, Maria; Mamedov, Aiaz; Soboleva, Anna; Trofimov, Dmitry; Fatkhudinov, Timur; Sukhikh, Gennady (Frontiers in Cell and Developmental Biology, 2023)
The role of the immune system in liver repair is fundamentally complex and most likely involves the spleen. The close connection between the two organs via the portal vein enables delivery of splenic cytokines and living cells to the liver. This study evaluates expression of inflammation-related genes and assesses the dynamics of monocyte-macrophage and lymphocyte populations of the spleen during the recovery from 70% hepatectomy in mice.The study used the established mouse model of 70% liver volume resection. The animals were sacrificed 24 h, 72 h or 7 days post-intervention and splenic tissues were collected for analysis: Clariom™ S transcriptomic assay, immunohistochemistry for proliferation marker Ki-67 and macrophage markers, and flow cytometry for lymphocyte and macrophage markers. This is a provisional file, not the final typeset articleThe loss and regeneration of 70% liver volume affected the cytological architecture and gene expression profiles of the spleen. The tests revealed significant reduction in cell counts for Ki-67+ cells and CD115+ macrophages on day 1, Ly6C+ cells on days 1, 3 and 7, and CD3+CD8+ cytotoxic lymphocytes on day 7. The transcriptomic analysis revealed significant activation of protease inhibitor genes Serpina3n, Stfa2 and Stfa2l1 and decreased expression of cell cycle regulatory genes on day 1, mirrored by inverse dynamics observed on day 7.Discussion and conclusion: Splenic homeostasis is significantly affected by massive loss in liver volume. High levels of protease inhibitors indicated by increased expression of corresponding genes on day 1 may play an anti-inflammatory role upon reaching the regenerating liver via the portal vein. Leukocyte populations of the spleen react by a slow-down in proliferation. A transient decrease in the local CD115+ and Ly6C+ cell counts may indicate migration of splenic monocytes-macrophages to the liver.